Literasi Psikologis Dalam Penataan Resolusi Intrapersonal Pada Permasalahan Perjudian - Setyawan, Erwin; Sasongko, Yohanes Probo Dwi (Indonesian Journal of Teaching and Teacher Education, 2025)
Our nation is facing a gambling emergency. The rampant phenomenon of gambling, both online and offline, has affected all aspects of life. The impact of gambling not only damages social relationships, economic needs, and mental health, but the loss of life is something precious that must be addressed. The massive impact is felt by many gamblers, especially online gamblers, who experience stress and mental disorders. Therefore, the purpose of this paper is to examine and further explain the psychological aspects of gambling. The method used is qualitative, with a netnographic study approach, which refers to the theory of consciousness transformation introduced by Reza Antonius Wattimena. In consciousness transformation, we can see that the main key to releasing attachment and dependence on gambling is to bring full awareness into human life. The results of the study show that with the existing level of awareness, we can have a good understanding that the phenomenon of gambling is a form of shared problem that we must pay attention to consciously and responsibly. This can be a way for humans to develop well and wisely in addressing every issue, especially those related to gambling.